Green cleaning as a tool in combating Covid-19: a content validity study for Malaysian healthcare facilities / Adriana Kamaruddin ... [et al.] - Kamaruddin, Adriana; Zainol, Nurul Nadiah; Sulaiman, Muhammad Azwan; Sukereman, Anis Syazwani; Abdullah Hashim, Hariati (UiTM Press, 2022)
Today’s healthcare industry continues to advance its efforts on cleaning and disinfecting while also effectively addressing COVID-19 and other harmful organisms. However, excessive exposure to hazardous cleaning and disinfecting products can itself endanger health. Many of the ingredients used in cleaning products could be very detrimental to the health of the cleaning workers, patients, and the environment. Thus, green cleaning plays a vital role in combating COVID-19 while protecting human health and the environment. This study aims to determine the components of green cleaning for healthcare facilities in Malaysia and how green cleaning contributes to human health and prevents expected environmental consequences of conventional cleaning practices. A content validity study was conducted involving eight green cleaning expert panels. This paper is anticipated to provide an initial guideline for healthcare facilities in Malaysia in a structured way in practising green cleaning during the pandemic.